ANALYSIS OF SMALL MARKETS LOCATED IN HISTORICAL NEIGHBORHOOD CENTERS LOCATED IN THE CITY OF SAMARKAND (Emergent: Journal of Educational Discoveries and Lifelong Learning (EJEDL), 2025)
A number of complex issues related to the preservation of architectural monuments, providing them with a street system, urban planning structure, their reconstruction, landscape design for tourist purposes and a variety of uses should be included. These issues are extremely relevant and require in-depth research and design development by the architect in solving them.